2003
DOI: 10.1046/j.1444-2906.2003.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition and deposition of cultured yellowtail Seriola quinqueradiata muscle at different anatomical locations in relation to meat texture

Abstract: The present study was undertaken to assess the lipid composition and deposition in muscle at three anatomical locations in cultured yellowtail and to investigate the effect of lipid composition and deposition on meat texture. Lipid deposition in muscle was studied by histochemical staining of lipid with Sudan dye. Lipid class composition analysis showed that neutral lipids were the main constituents of lipid in cultured yellowtail and accounted primarily for the variation in muscle lipid content with the anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 27 publications
4
3
0
Order By: Relevance
“…Similar results were described also in gilthead sea bream under fasting and refeeding conditions, thus suggesting a valuable applicability of the calpains as markers for flesh quality analysis [37]. Our results were consistent with previous reports on negative correlation between muscle texture and fat content [64,65]. Fish under voluntary swimming and fed with the HE diet presented significantly higher lipid deposition in muscle [5] and lower values of maximal strength and elasticity, but these differences were not found in the exercise condition.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were described also in gilthead sea bream under fasting and refeeding conditions, thus suggesting a valuable applicability of the calpains as markers for flesh quality analysis [37]. Our results were consistent with previous reports on negative correlation between muscle texture and fat content [64,65]. Fish under voluntary swimming and fed with the HE diet presented significantly higher lipid deposition in muscle [5] and lower values of maximal strength and elasticity, but these differences were not found in the exercise condition.…”
Section: Discussionsupporting
confidence: 92%
“…This effect was probably due to the opposite changes in collagen content. A negative correlation between the texture characteristics and muscle fat content was mentioned by Thakur et al [16] The results of this study were in agreement with them. The collagen of DSW-cultured orbicular batfish skin was easily solubilized by limited pepsin and the yield was very high, reaching 52.38% on a dry weight basis comparing to that of the SSW-cultured orbicular batfish skin (33.96%), DSW-cultured dorsal meat (4.21%, wet weight basis), and SSW-cultured dorsal meat (3.37%).…”
Section: Proximate Composition (%) Of Fish Meat and Skinsupporting
confidence: 93%
“…The influence of fat content in the muscle on the texture of the fillet is shown in Table 2 . Texture studies on different fish species have reported a significant loss of hardness, and hence a softening of the flesh associated with the increment of the fat content (Ginés et al., 2004 ; Ingebrigtsen et al., 2014 ; Másílko et al., 2015 ; Menoyo et al., 2004 ; Thakur et al., 2003 , 2009 ). This relationship associated with a fattier flesh, even when it is not systematically observed, always leads to a softer texture (Lefevre et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, mutually, the size and lipid content of the muscle fibers contributed to the mechanical resistance of the raw fillet; not only the particular responsibility of adipocytes with less resistance to compression, but also the muscle fibers that are bathed in large amounts of lipid and can slide more easily across each other and generate less resistance (Aussanasuwannakul et al., 2011 ). The collagenous connective tissue structure can contribute to the structural weakening of the muscle (Thakur et al., 2003 ). Particularly, the highest proportion of intramuscular adipocytes, in the farmed fish muscle, located within the perimysium and myosepta, resulting in a mechanically less resistant tissue as compared with a lean tissue, rich in fibrous proteins (Lefevre et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation